Analisis Website mataharimall.com Menggunakan Metode WEBQUAL 4.0 (Studi Kasus Pelanggan Di Kota Batam) - Mesri Silalahi (Computer Based Information System Journal, 2015)
This study aims to measure the effect of the quality of each dimension of 4.0 to satisfaction WebQual website users MatahariMall.com in Batam. To answer these problems, researchers collecting data in the form of primary and secondary data. The data collection was done by using questionnaires (questionnaire). The population in this study is the customer in Batam ever access or shop through MatahariMall.com where total respondents involved in this research were 100 respondents. The amount is determined by quota sampling technique due to lack of time, effort, cost. The collected data is processed and analyzed using SPSS statistical application assistance 19. To get an idea of ​​the quality of the website MatahariMall.com researchers conducted a descriptive analysis. Subsequent analysis is the analysis of verification is to measure the effect of each variable to the satisfaction of website quality. There is a positive and significant impact Usability (ease of use) to user satisfaction (user satisfaction). There is a positive and significant impact Information quality (quality information) to user satisfaction (user satisfaction). There is a positive and significant influence Service interaction quality (quality of service) to user satisfaction (user satisfaction).